2015
DOI: 10.1039/c5ra12925g
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of novel unsymmetrical azines as quorum sensing inhibitors

Abstract: In this report, novel unsymmetrical azines have been designed and synthesised by using one pot approach. Further, they were evaluated as quorum sensing inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 51 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…As mentioned earlier, both of the assayed traits are under the control of QS. 20 , 21 Interestingly, we found that albendazole has anti-QS activities in sub-MICs in a dose-dependent manner. Therefore, it can inhibit violacein production in C. violaceum .…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…As mentioned earlier, both of the assayed traits are under the control of QS. 20 , 21 Interestingly, we found that albendazole has anti-QS activities in sub-MICs in a dose-dependent manner. Therefore, it can inhibit violacein production in C. violaceum .…”
Section: Introductionmentioning
confidence: 74%
“…We have performed this assay as previously described in one of our work. 20 In test tubes, 10 mL of LB broth was inoculated with plasB-gfp ( ASV) strain and was kept in incubation (overnight (O/N), 37 °C). An O/N growth culture was diluted 1:40 (about 125 µL of O/N culture was added to 4.875 mL of LB broth).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbones with the general formula (NHC) → C ← (NHC) were theoretically designed, later generated and proven to carry interesting chemical bond characteristics . Compounds with the general formula (NHC) → E ← (NHC) (EBH, C, Si, Ge, and P ⊕ ), (I) and compounds with the general formula (NHC) → E–E ← (NHC) (E–EB 2 , Si 2 , Ge 2 , N 2 , P 2 , As 2 , N‐P), (II) were reported (Fig. ).…”
Section: Introductionmentioning
confidence: 99%